Behind the Iron Curtain in Poland – A Personal Memoir. Issue 2 (2nd April 2020) - Thorpe, Nigel
ABSTRACT: This memoir outlines the experience and observations of Nigel Thorpe, a British diplomat in Poland in the 1970s and 1980s, in a Cold War context. It touches unrest in Gdansk, Szczecin, and Łódz, changes in the leadership and policy of the Communist Party, and unexpected changes in relations with West Germany. After 13 years, Thorpe returned to a Poland changed by martial law and Solidarity and a people at odds with their rulers. He relates his first meeting with Lech Wałęsa and the steady development of contacts with Solidarity, with the role of the BBC, the Catholic Church, and the alternative underground society. Although the Warsaw Diplomatic Corps wondered if Solidarity was finished, the British view differed. He discusses the historic visit of Prime Minister Margaret Thatcher in November 1988, highlighting her advice that Wałęsa should take part in the proposed Round Table talks. The finale involved the repatriation of the remains of Marshal Władysław Sikorski to a free and democratic Poland in 1993.